Effect of dietary tryptophan supplementation on growth, body composition and digestive enzymes activity of juvenile silver pompano Trachinotus blochii (Lacepede, 1801) - Devassykutty, Meenu; Ignatius, Boby; P, Vijayagopal; Ebeneezar, Sanal; Sawant, Paramita; A. M., Babitha rani; Varghese, Eldho; P, Sayooj; K.A, Sajina (Indian Journal of Fisheries, 2022)
A 60-day feeding trial was conducted to study the effect of dietary supplementation of tryptophan in juvenile silver pompano Trachinotus blochii (Lacepede, 1801) (Average initial weight=6.81±0.05 g). Five isonitrogenous and isolipidic feeds supplemented with tryptophan at different levels, 0 (TRP0), 0.5 (TRP0.5), 1.0 (TRP1.0), 1.5 (TRP1.5) and 2.0 (TRP2.0) g 100 g-1 of diets were formulated. The weight gain%, specific growth rate, hepato-somatic index, digestives enzymes of stomach and intestine except protease activity in stomach, red blood cells, white blood cells, crude protein, fat and ash content of the fish were significantly influenced (p<0.05) by tryptophan supplementation. The viscero-somatic index, intraperitoneal fat ratio, muscle ratio, protease activity in the stomach and acid insoluble ash were unaffected by the treatment. Best observations in terms of growth, body composition and digestive enzyme activity among the treatments were obtained in the fish group fed with tryptophan at a level of 0.5 g 100 g-1 feed. From the current observations it can be concluded that supplementation of tryptophan at the rate of 0.5 g 100 g-1 diet can positively influence the growth of T. blochii. Keywords: Essential amino acids, Growth, Silver pompano, Tryptophan